FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN PANGKEP - Megawati Megawati; Tjipto Djuhartono; Khoirul Umam (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This study aims to determine the factors that affect the effectiveness of the implementation of land and building tax management in the Regional Financial and Asset Management Revenue Service (DPPKAD) of Pangkep Regency study uses which has three indicators, namely input, Throughput, and output. This research method is descriptive qualitative by using field research through observation, techniques in data collection are observation, interviews, and prime and secondary documentation, primary data sources in the form of informants totaling as many as five people, consisting of heads of BPHTB and PBB-P2 DPPKAD, BPHTB and PBB-P2 Kasi, UN Village officers (collectors) and the community as taxpayers. The results of this study found that factors affecting the effectiveness of land and building tax management in the Regional Financial and Asset Management Revenue Service (DDPKAD) of Pangkep Regency, the input component has not been effective, while the throughput component can be said to be effective, and the output component has not been effective. And some obstacles are still found in the Land and Building Tax bill, both from taxpayers and from tax officers as well as clarity and legal certainty at the Pangkep Regency Revenue Management Office, Finance and Assets.